COMPARATIVE ASSESSMENT OF QUALITY OF IMMUNORADIOMETRIC ASSAY (IRMA) AND CHEMILUMINESCENCE IMMUNOMETRIC ASSAY (CHEIMA) FOR ESTIMATION OF THYROID STIMULATING HORMONE (TSH) - Sajid, K. M. (The Nucleus, 2020)
Biological substances like hormones, vitamins and enzymes are found in minute quantities in blood. Their estimation requires very sensitive and specific methods. The most modern method for estimation of thyroid stimulating hormone in serum is non-isotopic enzyme enhanced chemiluminescence immunometric method. In our laboratory immunoradiometric assay is in routine for the last many years. Recently interest has grown to establish non-isotopic techniques in laboratories of PAEC. However, the main requirement to adopt the new procedures is to compare their results, cost and other benefits with the existing method. Immunoassay laboratory of MINAR, therefore, conducted a study to compare the two methods. A total of 173 (males: 34 females: 139 age: between 1 and 65 years) cases of clinically confirmed thyroid status were included in the study. Serum samples of these cases were analyzed by two methods and results were compared by plotting precision profiles, correlation plots and calculating sensitivities and specificities of the methods. As the results in all the samples were not normally distributed Wilcoxon rank sum test was applied to compare the analytical results of two methods. The comparison shows that the results obtained in two methods are not completely similar (p=0.0003293), although analysis of samples in groups shows that some similarity exists between the results of hypo and hyperthyroid patients (p<=0.156 and p<=0.6138). This shows that results obtained in these two methods could sometimes disagree in final diagnosis. Although TSH-CHEIMA is analytically more sensitive than TSH-IRMA the clinical sensitivities and specificities of two methods are not significantly different. TSHCHEIMA test completes in almost 2 hours whereas TSH-IRMA takes about 6 hours to complete. Comparison of costs shows that TSH-CHIEMA is almost 5 times more expensive than TSH-IRMA. We conclude that the two methods could sometimes disagree but the two techniques have almost same clinical efficacy (clinical usefulness). The clinical sensitivities and specificities are similar and TSH-IRMA is in no way inferior to the non-isotopic method. It is, therefore, not reasonable to abandon a good technique only for relatively speedy results.